ANALISIS POLA PEMBELIAN PRODUK KEBERSIHAN DI SWALAYAN SALAFIYAH SYAFI’IYAH MENGGUNAKAN ALGORITMA K-MEANS - Moh. Zaini Romly; Zaehol Fatah (CV. Denasya Smart Publisher, 2024)
The rapid development of technology in Indonesia has had a significant impact on various sectors, including the retail sector which is increasingly adopting computerized systems in the transaction process. Supermarket Salafiyah Syafi'iyah is one example of a supermarket that utilizes computerization to optimize product arrangement and analyze consumer purchasing patterns. Identification of purchasing patterns of hygiene products at Supermarket Salafiyah Syafi'iyah was carried out using quantitative methods. Data were collected through observation and processed using association rules to find patterns of association between hygiene products that are often purchased together. The application of the K-Means algorithm as a Data Mining technique can help improve business performance, such as making consumers interested in buying products. It was identified that there were certain items with high support and confidence values, which indicated a significant purchasing pattern for certain hygiene products at this supermarket.